Overcoming cross‐cultural barriers to knowledge management using social media. Issue 1 (2014) - ,
Abstract : Purpose – The purpose of this paper is to examine the barriers to knowledge management (KM) due to various national cultural dimensions and to understand how social media can be used to mitigate those barriers to KM processes within organizations.Design/methodology/approach – The paper begins with a focussed review of existing literature to understand the key concepts in KM and national culture. The paper then outlined the important dimensions of national culture and the barriers they introduce to the KM processes. The paper also briefly reviews the features of some of the popular social media tools available. The paper then conceptually link the three areas of KM, national culture and social media to emerge with a clear picture of how social media can overcome KM barriers due to specific cultural traits.Findings – National culture has multiple dimensions and each of these dimensions can act as a significant barrier to KM within organizations. Social media tools have rich interactive features which can help overcome these barriers. Choosing the correct social media tool with specific features can help alleviate the issues introduced by specific cultural traits.Originality/value – This paper integrates the three areas of KM, national culture and social media. It provides an understanding of how the various cultural dimensions can act as barriers to KM. It particularly outlines specific social media tools to remedy obstacles to KM due to each of the national culture dimension.